Global updated rangeland ecosystem climate change projections through 2050, using evaluated parameters and CMIP6 climate forecasts - Hussein, Jason; Thornton, Philip K. (International Livestock Research Institute, 2024)
Climate change in rangelands creates uncertainty that hinders the long-term direction of research, land management, agricultural production and policy formulation. The updated rangeland ecosystem projections under climate change use the most recent global climate forecasts (Coupled Model Intercomparison Project CMIP6) with evaluated model parameters for the G-Range global rangeland simulation model to project how rangeland ecosystems may change through 2050. The spatial dataset produced includes several fundamental attributes of rangeland ecosystems, specifically net primary productivity, soil carbon, cover of grass, shrubs, trees and bare soil, and root:shoot ratio on a decadal basis. G-Range was driven by climate inputs produced using MarkSimGCM, specifically CMIP6 from 2001 to 2050, and historical data from 2001 to 2020. These outputs are used as inputs to other models and analyses, or for national to global scale estimates of rangeland ecosystem status, structure and function under climate change, with significant implications for research, land management, agricultural production and policy formulation and implementation.